Central Contrast Sensitivity as an Outcome Measure in Randomized Controlled Trials in Glaucoma—A Systematic Review - Alexander Sverstad; Jens Riis Møller; Gianni Virgili; Augusto Azuara-Blanco; Josefine Freiberg; Simone Ahrensberg; Olav Kristianslund; Goran Petrovski; Miriam Kolko (Life)
Purpose: Standard automated perimetry (SAP) remains the gold standard functional test in glaucoma, used primarily for evaluating peripheral vision loss. Central contrast sensitivity (CCS) has emerged as a potential early functional marker of glaucomatous damage. This systematic review aimed to describe the different methods used to measure CCS in randomized controlled trials (RCT) involving glaucoma patients. Methods: We searched the MEDLINE, Embase, CINAHL, Cochrane Central Register of Controlled Trials, Epistemonikos, and ClinicalTrials.gov databases on 25 January 2023, and updated the search on 12 February 2025. Eligible studies comprised RCTs that reported CCS as an outcome in patients with glaucoma, suspected glaucoma, or ocular hypertension. No restrictions were placed on age, sex, ethnicity, geography, intervention, or publication year. Abstracts and full texts were screened independently by two reviewers. Descriptive statistics were used. No formal risk of bias assessment was performed, due to the descriptive nature of the review. Results: Of 1066 records screened, 31 studies met the eligibility criteria. The study sample size ranged from 7 to 207 (median: 23), with most studies involving primary open-angle glaucoma. Interventions were diverse, mainly involving topical medications, with timolol being the most frequent. Eleven CCS test methods were identified. Five studies did not report the method used. The CSV-1000 was the most commonly used test, being applied in 11 studies. Conclusions: CCS has been measured using a wide range of methods in glaucoma RCTs, with limited standardization. Most of the included studies were small, variably reported, and conducted over 10 years ago, suggesting a decreasing interest in CCS as an outcome measure in glaucoma RCTs. Funding: This review was funded by Oslo University Hospital and the Research Council of Norway. Registration: This review was registered on the OSF.